Advances in Computing and Communications First International Conference, ACC 2011, Kochi, India, July 22-24, 2011, Proceedings, Part III - Abraham, Ajith; Mauri, Jaime Lloret; Buford, John F.; Suzuki, Junichi; Thampi, Sabu M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This volume is the third part of a four-volume set (CCIS 190, CCIS 191, CCIS 192, CCIS 193), which constitutes the refereed proceedings of the First International Conference on Computing and Communications, ACC 2011, held in Kochi, India, in July 2011. The 70 revised full papers presented in this volume were carefully reviewed and selected from a large number of submissions. The papers are organized in topical sections on security, trust and privacy; sensor networks; signal and image processing; soft computing techniques; system software; vehicular communications networks.
Keywords: Computer science; Computer Communication Networks; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Information Systems; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Systems Applications (incl.Internet).; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Management of Computing and Information Systems